2019
DOI: 10.3389/fimmu.2019.01546
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 Protein Expression in Mild and Severe Lupus-Prone Models Is Regulated in a Leukocyte, Genetic, and IRAK4 Dependent Manner

Abstract: The global increase in autoimmunity, together with the emerging autoimmune-related side effects of cancer immunotherapy, have furthered a need for understanding of immune tolerance and activation. Systemic lupus erythematosus (SLE) is the archetypical autoimmune disease, affecting multiple organs, and tissues. Studying SLE creates knowledge relevant not just for autoimmunity, but the immune system in general. Murine models and patient studies have provided increasing evidence for the innate immune toll like re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 74 publications
0
21
0
Order By: Relevance
“…Studies involving animal models have shown that TLR7 is involved in the pathogenesis of glomerulonephritis, including lupus nephritis and diabetic nephropathy; agonists of TLR7 aggravate glomerulonephritis symptoms in both diseases, while the blockade of TLR7 could alleviate renal injury (61-64). High renal TLR7 expression has been detected in both lupus-prone mice and a diabetic animal model, and it is closely related to the production of proinflammatory cytokines (e.g., IL-6, IL-1β, TNF-α, and IL-12) and consequent renal injury (61,(63)(64)(65). The infiltration of B cells and increased expression of TLR7 has been demonstrated in kidney specimens of patients with lupus nephritis (25,26,66).…”
Section: Table 2 Association Of Fluorescence Intensities Of Intrarenmentioning
confidence: 99%
“…Studies involving animal models have shown that TLR7 is involved in the pathogenesis of glomerulonephritis, including lupus nephritis and diabetic nephropathy; agonists of TLR7 aggravate glomerulonephritis symptoms in both diseases, while the blockade of TLR7 could alleviate renal injury (61-64). High renal TLR7 expression has been detected in both lupus-prone mice and a diabetic animal model, and it is closely related to the production of proinflammatory cytokines (e.g., IL-6, IL-1β, TNF-α, and IL-12) and consequent renal injury (61,(63)(64)(65). The infiltration of B cells and increased expression of TLR7 has been demonstrated in kidney specimens of patients with lupus nephritis (25,26,66).…”
Section: Table 2 Association Of Fluorescence Intensities Of Intrarenmentioning
confidence: 99%
“…TLR7 is involved in the development of SLE upon activation by RNA-containing immune complexes and is important for SLE pathogenesis through participation in inflammatory signal transduction [ 40 ]. Recent studies have shown increased signaling through TLR7 in SLE and the elevated mRNA expression of TLR7 and TLR9 in PBMCs of patients with SLE [ 42 ]. To date, genome-wide association studies, in vitro studies, experimental mouse models, and clinical sample analysis have provided relevant evidence on the involvement of TLRs, including TLR7/9, in SLE onset.…”
Section: Discussionmentioning
confidence: 99%
“…The TLR7 gene, which is located at chromosome X, has recently been the focus of considerable research in SLE and LN. Theories regarding the contribution of TLR7 gene have included 1) Enhanced TLR7 protein expression in renal DCs and macrophages which correlated with renal disease parameters in murine models [42] 2) Emerging evidence that TLR7 dosage is a key pathogenic factor to the pathogenesis of SLE: Dillon et al assembled the largest group consisting of 316 men with SLE and found high prevalence of SLE in X chromosome aneuploides such as Klinefelter's syndrome (KS; 47, XXY) and de la Chapelle's syndrome (46, XX male) [43] while recently, Souyris and colleagues provided proof that TLR7gene evades X chromosome inactivation in immune cells in women and KS men, and proposed this as a mechanism for the elevated risk of SLE in women and KS [44], which may partially explain the high preponderance of SLE in females.…”
Section: Pathogenesismentioning
confidence: 99%